Determination of Maximum Tolerated Dosage of Huang Lian in Mice and its Effect on Mouse Intestinal Bacteria Population: Quantitative Analysis of Bifidobacteria Species - Ng, Adelyn Yih Jia (2015)
Bifidobacterium can inhibit the growth of harmful bacteria and boost the immune system while Huang Lian is the Traditional Chinese Medicine with cold in nature and bitter in taste can use for heat clearance, detoxification and clear dampness. The aim of this study was to quantitatively analyze the impact of HL or HL with Xiang Sha Liu Jun Zi decoction (XSLJZ) on gastrointestinal Bifidobacterium population. The model rats were force fed with low dose (65mg/kg), moderate dose (250mg/kg) for duration of 4 weeks. Weight of mice was measured at 1st and 4th week. The general appearance of mice was observed daily. Administration low dose of HL for 4 weeks could increase significantly Bifidobacterium population. Weight increased in combination group was significantly higher than HL group. There were no obvious changes on the appearance of mice. Low dose of HL could promote the growth of Bifidobacterium. XSLJZ could enhance the function of HL to promote normal growth of mice.